TINJAUAN HUKUM TERHADAP PELAKSANAAN PENYIDIKAN TINDAK PIDANA DI BIDANG PERPAJAKAN MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2007 - Damanik, Rudang Sari Ayu; Na’im, Khairun; Sitepu, Karolina; Darma, Mospa (CV Widina Media Utama, 2024)
This research aims to conduct a legal review of the implementation of criminal investigation in the field of taxation based on Law Number 28 of 2007. The main focus of this study is to analyze the legal provisions regulating the process of criminal investigation in taxation and evaluate its implementation in practice. The research methods used include legal document analysis, literature review, and field research to gain a comprehensive understanding of the taxation investigation mechanism.The results of the research indicate that the implementation of the investigation illustrates that the process of conducting criminal investigations in taxation, as regulated by Law Number 28 of 2007, involves a series of stages from administrative examination to investigation. The authority of tax investigators, as mandated by the law, grants broad powers to conduct examinations and investigations without the involvement of the police, including the execution of searches and seizures with court permission. In its implementation, there are challenges that need to be addressed. Dependence on the police, interventions, pressure from certain parties, as well as limitations in human resources and the qualifications of tax investigators are factors that can hinder the effectiveness of the investigation. The phenomenon of